The Various Possible EU Taxes - Raluca-Andreea Mihalache (CES Working Papers, 2012)
In this article, the various possible EU taxes are compared with regard to each of the criteria: budgetary, equity and efficiency criteria. In principle, this problem of revenue insufficiency can be overcome by combining several resources, including contributions from the Member States, to make up for the needs of the EU budget Setting an equalisation mechanism to replace or complement the current GNI contribution could thus be a useful complement to tax autonomy in the context of a reform of the current own resource system.
Keywords: C10; E62; H30; O23; 330; accession by the EU; accounting methods; budgetary criteria; efficiency criteria; equity criteria; fiscality; tax basis; tax rate Romania